Disclosure of medical error to parents and paediatric patients: assessment of parents' attitudes and influencing factors. Issue 4 (29th November 2009) - Matlow, A G; Moody, L; Laxer, R; Stevens, P; Goia, C; Friedman, J N
Abstract : Objective: To assess parental preferences for medical error disclosure and evaluate associated factors. Design: Prospective survey. Setting: Hospital for Sick Children, Toronto, Canada. Participants: Parents of inpatients and outpatients. Main exposure: Anonymous questionnaire administered on May to August 2006, surveying demographic characteristics and identifying parents' thresholds for disclosure using a vignette with six levels of harm. Main outcome measures: Preferred thresholds for parent and patient disclosure and associated factors. Results: 99% of 431 parents (181 inpatients, 250 outpatients) wanted disclosure if there was potential or actual harm versus 77% if there was none (p<0.0001). Most parents (71% vs 41%) wanted their child similarly informed (p<0.0001). Parental age, education, experience with error and child's age did not affect preferences for disclosure. Parents of inpatients (p=0.03, OR 1.65, 95% CI 1.04 to 2.62) and those born in Asia (vs North America) had a lower disclosure threshold (p=0.014, OR 2.4, 95% CI 1.2 to 4.9), and administering the survey with increasing harm had a higher disclosure threshold (p<0.0001, OR 2.46; 95% CI 1.58 to 3.83). Experience with error: (p=0.05, OR 1.5, 95% CI 1 to 2.2) and child age (eg, ≤6 years vs ≥ 11 years (p<0.0001, OR 2.74, 95% CI 1.73 to 4.33)) directly affected preferences for informing the child. Asian parents had a lower threshold for informing the child than North American parents. Conclusions: Most parents want disclosure and want their child informed of errors with harm. While parental birth country, experience with error and patient age influenced parents' desire for disclosure to their child, the details of disclosure warrant study.